THE SUBTLE PORTION IN WRITING WITHIN THE EXPERIENCE OF THE INVENTED PLACE (Palíndromo, 2016)
Aspects of the writing, found throu- ghout the textual production of the artis- tic research, open the possibility to think about the writing experience articulated within contemporary artistic procedures. Departing from relationships between the writing process and the uses of me- thodologies of scientific production, the place the writing develops is unfolded by the reading of The Zen Art and the Emp- ty Way: A research about the zen-budist concept of Non-Self in the artistic crea- tion, art thesis written by Claudio Miklos.
Keywords: artistic research; writing; scripture; territory